PENDAMPINGAN DALAM DIVERSIFIKASI UBI JALAR UNTUK MENINGKATKAN PEREKONOMIAN KELUARGA - Kartika, Rika; Hartoko, Gatot; Ni’mah, Ratu Sifa; Assyifa, Assyifa; Safitri, Esti (LPPM Universitas Bina Bangsa, 2024)
This community service activity aims to provide assistance to women in the verification of sweet potatoes to improve the family economy by create new business opportunities because there is still a lack of innovation from the use of natural products by the community. There are several methods carried out in this activity, namely counseling, mentoring, and field surveys for the sale of finished products. This community service activity is important because it can provide insight to the community about diversifying natural products, can create business opportunities, and can benefit from sales, so as to improve economic welfare. In the trial sales stage, the results of diversifying purple sweet potatoes into melted sweet potato balls obtained 100% sales results according to the target